2017
DOI: 10.1111/trf.14097
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evidence for underreporting of male‐to‐male sex among human immunodeficiency virus–infected donors in the Netherlands and Flanders

Abstract: HIV typing helps to understand HIV transmission routes in donor populations. We found substantial underreporting of male-to-male sex among HIV-infected male donors. Donor education on HIV risk factors and the danger of window-period donations and a donor environment that encourages frank disclosure of sexual behavior will contribute to a decrease of HIV-infected donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
5
0
2
Order By: Relevance
“…Noteworthy was that the majority of MTCs found the number of MSM clearly outweighed the number of heterosexuals, and in many, only men were represented. This observation is in line with that reported in previous studies and suggests that misreporting of transmission risk may be an important reason for the presence of mixed clusters [ 10 , 37 , 38 ]. The most important reason for misreporting could be fear or embarrassment to disclose sex with same-gender sex.…”
Section: Discussionsupporting
confidence: 93%
“…Noteworthy was that the majority of MTCs found the number of MSM clearly outweighed the number of heterosexuals, and in many, only men were represented. This observation is in line with that reported in previous studies and suggests that misreporting of transmission risk may be an important reason for the presence of mixed clusters [ 10 , 37 , 38 ]. The most important reason for misreporting could be fear or embarrassment to disclose sex with same-gender sex.…”
Section: Discussionsupporting
confidence: 93%
“…However, TC6 encompassed sequences isolated in several countries, indicating a larger geographical spread. The disparity seen in TC5, composed only by males but mainly reporting heterosexual transmission route can be explained by the previously described MSM under-reporting 49,50 . Furthermore, “missing-links” can still exist, related to unavailable data that could help explain this disparity.…”
Section: Discussionmentioning
confidence: 92%
“…Second, we showed that clustering was associated with younger donors, with a recent infection, and infected with HIV-1 subtype B, which are characteristics more likely associated to the HIV+ MSM population in France. 17,31 Our results showed that 34.3% of MSM male BDs on a declaration basis were part of robust MSM clusters. This is exactly the same figure as found for MSM individuals in PRIMO.…”
Section: Discussionmentioning
confidence: 65%